PECULIARITIES OF MANIFESTATION OF HOSTILITY IN STUDENTS WITH DIFFERENT LEVELS OF SUBJECTIVE WELL-BEING (Psychology Travelogs, 2024)
The analysis of the mental state of students is an important and relevant area of modern psychological research. This can be explained by the special conditions in which they are forced to receive education. Over the past few years, a significant majority of higher education institutions have switched to a blended learning format due to objective circumstances in society. Understanding how and in what way the level of subjective well-being affects the mental state of a person, including manifestations of hostility, creates new opportunities for correcting the manifestations of this condition among students.Based on the theoretical analysis of sources describing the phenomena of hostility and subjective well-being, it can be assumed that these factors are interrelated. This is explained by the fact that subjective well-being is a multifaceted structure of the psyche that manifests itself in a significant number of spheres of human life. Hostility, in this case, should be regarded as a full-fledged life attitude of a person, which can be a continuation of the general negative worldview of a person, formed as a result of a low level of subjective well-being.The empirical study was aimed at investigating the main trends in the development and formation of hostility and the state of subjective well-being among students. The sample included 93 respondents, of whom 48 were women and 45 were men.The results of this study contain important information about the peculiarities of correction of negative manifestations of hostility in students with a low level of subjective well-being.
Keywords: hostility; subjective well-being; mental state; psychology of students